Study on mechanical properties and corrosion behavior of porous magnesium alloy for biomedical application - Nurul Husna Zakaria (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2015)
The present study was carried out to develop porous Mg alloy from elemental powder (Mg alloy and ammonium bicarbonate (NH4HCO3) through powder metallurgy method based on the space holder technique. This technique utilizad two phase of sintering process which is to heat treated the sample at low temperature to burn out the space holder to create pores and eventually sintered at high temperature. The aims of this research are to investigate the effect of processing parameters on the porosity, density, microstructure and mechanical properties of fabricated porous Mg alloy body.